"Breaking through the Foul and Ugly Mists of Vapours"— Regulation of Alternative Tobacco and Related Products by the New TPD and Exercise of EU Competence. Issue 6 (6th November 2018) - Abaquesne de Parfourus, Anatole
Abstract: Directive 2014/40—the new Tobacco Products Directive—was unsuccessfully challenged in three cases, Philip Morris, Poland v. European Parliament and Council, and Pillbox 38 . This Article examines provisions of the Directive relating to some alternative tobacco and related products, both in terms of exercise of EU competence and substantive regulation of these products. The main flavored tobacco products can no longer be placed on the market. Electronic cigarettes are regulated by the Directive, as the initial provisions of the Commission proposal were substantially amended. The new Tobacco Products Directive reproduced the prohibition of tobacco for oral use, already at issue in the Swedish Match and Arnold André cases, and again subject of another preliminary ruling reference by Swedish Match, the Advocate General's Opinion having concluded in its validity. The Directive also provides the possibility for Member States to prohibit categories of tobacco or related products. Parallel to its analysis of their substance in terms of health regulation, this Article considers European Union competence issues relating to these provisions and examines the adequacy of the Article 114 TFEU internal market legal basis as well as compliance with the principles of proportionality and subsidiarity.